Statistical Survey: the Proportion of Students Willing to Become Teachers of Mathematics - Januškevičius, Romanas; Pumputis, Dalius (Pedagogika, 2015)
The article discusses the problems of mathematical literacy of graduates from secondary schools as well as the problems related to the increasing gap between higher and secondary education institutions in Europe and in Lithuania, whereof education system has been undergoing the reform. The results of a statistical survey, which was carried out in Lithuanian University of Educational Sciences, are also presented. The survey focused on the analysis of the answers of the selected population of students to the question ‘What is the proportion of students willing to become teachers?’ The answer to this question has received highly controversial evaluations from specialists of the Ministry of Education and Science of the Republic of Lithuania, who administer financing of universities, on the one hand, and specialists in educational science, who have been conducting the aforesaid surveys and research, on the other hand. The simple statistical analysis and some methods of survey sampling were applied to solve this problem. Differently from the situation of earlier years, the survey results show that nowadays the above-mentioned proportion of students is growing.